A Study to Evaluate Students' Performance, Engagement, and Progression in Higher Education Based on Feedforward Teaching Approach - Nagham Saeed; Fehmida Mohamedali (MDPI AG, 2022)
Learners who enter higher education (HE) at the foundational level are susceptible to many challenges that impact their performance, engagement, and progression. Not all students who enter HE at the foundational level will progress and attain their course qualifications. In addition, many university lecturers struggle to give effective support to their students. This study focuses on feedforward teaching approaches that define ways to enhance learning by using advanced organisational strategies to offer relevant supporting concepts and meaningful verbal material. To date, there are insufficient literature reviews on feedforward approaches to facilitate students' subsequent learning. Providing better academic support for students and a strong foundation for independent learning is the focus of this paper. Therefore, the main contributions of this paper are identifying the key feedforward features and suggesting effective feedforward approaches. This study was undertaken to rigorously implement feedforward approaches that would support groups of students in modules at the foundational entry-level. At the end of module delivery, different students' data sets were analysed related to the progression rates, standard deviation, and mean. In addition, the student satisfaction questionnaire (module evaluation survey) and feedback survey were also considered for engagement and retention purposes. The outcomes from this exercise suggest that feedforward approaches allow students to increase their overall effort when attempting summative assessments and, thus, improve their performance, engagement, and retention.